2013
DOI: 10.1177/1350507613483421
|View full text |Cite
|
Sign up to set email alerts
|

‘I don’t know what I am doing!’: Surfacing struggles of managerial identity work

Abstract: Recent work contends that management education provides an important space for managers' identity work. However, it is also recognised that much of what is currently offered constrains rather than enables managers' identity work. Against this background, I present material which provides important practical possibilities to managers for more realistic and helpful forms of identity work, and theoretically also add to the development of a more nuanced understanding of managerial identity work processes. Drawing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
123
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(129 citation statements)
references
References 69 publications
1
123
0
5
Order By: Relevance
“…The first stage of analysis was developed by reading and rereading the fieldnotes and reflexive diaries, reflecting on which experiences were most salient (Hay, 2014). The second stage involved crafting these experiences into ethnographic stories.…”
Section: Introducing Creative Artsmentioning
confidence: 99%
“…The first stage of analysis was developed by reading and rereading the fieldnotes and reflexive diaries, reflecting on which experiences were most salient (Hay, 2014). The second stage involved crafting these experiences into ethnographic stories.…”
Section: Introducing Creative Artsmentioning
confidence: 99%
“…A person's profession represents much more than their aptitudes and functions; it is a form of life to be assumed, as the relation between the workers and their profession is characterized by the engagement and by the feeling of identity and compliance with its attributes. The professional identity, therefore, plays a vital role in how individuals give meaning to our work environment and manage their careers; it is an important input for the construction of work identity (Dubar, 2015;Hay, 2014;Miscenko & Day, 2016).…”
Section: Analysis Of the Professions Under The Students' Eyes: A Possmentioning
confidence: 99%
“…Arenas that are not created by the organization, and therefore not under its control, become a safe space [76][77][78] because the exchange of support is under the control of the individual manager.…”
mentioning
confidence: 99%
“…Previous research has shown that managerial courses facilitates the acquisition of social support [31,[46][47][48]. Management programmes have also been suggested to be safe spaces, separated from managers' daily work, that allow them to build or strengthen their identity as managers, because they are reluctant to entrust or allow their workplace to be a part of that identity work [48,[77][78]. In this study vocational courses were an important arena for access to social support, as they gave the managers knowledge and information and facilitated valuable discussions.…”
mentioning
confidence: 99%
See 1 more Smart Citation